WALANT - EFFICIENT AND SAFE TECHNIQUE - KEY TREATMENT IN COVID-19 PANDEMIC - Madalina-Cristina Fotea; Stefana Luca; Dorin Alexandru Sumanaru; Oxana Madalina Grosu; Andra Bulgaru Iliescu; Alexandru Filip; Mihaela Poroch; Vladimir Poroch; Roxana Maria Pinzaru; Claudiu Carp; Mihaela Mitrea (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study The aim of the study was to confirm the effectiveness and safety of wide awake local anesthesia no tourniquet (WALANT) technique in hand surgery, as well as its necessity and importance during the COVID-19 pandemics. Material and methods A retrospective study was performed between March 2020 and September 2021 to evaluate advantages of WALANT, taking into consideration the rules imposed by the pandemic context. This study included 360 patients, treated for acute and chronic hand diseases. A statistical investigation was performed using SPSS 20.0 version software and applying the ANOVA regression, evaluating demographic, anatomical and surgical variables. Results: 234 males and 126 females, treated for acute hand trauma (metacarpal and phalanx fractures, tendon and nerves lesions) and chronic hand diseases such as carpal tunnel syndrome (CTS) dupuytren's disease (DD), trigger finger (TF), soft tissue and bone tumors. The average patient waiting time from admission in the operating room was 13.95 minutes, while the mean time of onset of local anesthesia was 12.15 minutes. No complications such as distal digital bleeding, hematoma, the necessity of using the antidote, or necrosis occurred, the outcomes were very good and the patient satisfaction high. Conclusions: The WALANT technique can be considered the "gold standard" in hand surgery anesthesia during the COVID-19 pandemic, ensuring a correct and safe surgical treatment in the restrictive conditions imposed by the epidemiological context.